Pengaruh Leverage Terhadap Profitabilitas Pada PT.Pabrik Kertas Tjiwi Kimia Tbk - Devi, Shinta Prasetia; Haribowo, Siget Fitrianto; Damayanti, Vidya; Hamdani, Umar; Siswanto, Ely (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study examines the effect of leverage on the profitability of PT Pabrik Kertas Tjiwi Kimia Tbk during the 2020–2024 period. Using a causal research method with secondary data obtained from financial reports published on the Indonesia Stock Exchange (IDX), the study analyzes the relationship between Debt to Equity Ratio (DER) as the leverage indicator and Return on Assets (ROA) as the profitability indicator. The results indicate a significant negative relationship between leverage and profitability. Increased DER is associated with a decrease in ROA, suggesting that excessive debt reduces financial performance due to higher interest costs and financial risks. This study contributes to the understanding of leverage's impact on profitability in the manufacturing sector, offering valuable insights for corporate management, investors, and academics. Recommendations include enhancing operational efficiency and optimizing debt management strategies to improve long-term profitability